THE IMPORTANCE OF READING IN TEACHING THE RUSSIAN LANGUAGES TO STUDENTS - Lola Nazarova, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The article examines the role of reading in teaching foreign languages to students and its impact on vocabulary development, text comprehension, fluency, and motivation. Contemporary research in the Russian language teaching contexts demonstrates that both intensive and extensive reading positively influence linguistic, cognitive, and affective outcomes. Extensive reading fosters learner autonomy, engagement, and sustained interest in the language, while comprehension strategies enhance deeper understanding of texts. The study concludes that integrating structured reading activities and diverse texts into language curricula is essential for effective and holistic foreign language acquisition.